2023
DOI: 10.1021/acsami.3c08042
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Coating Graphene Oxide and Silanes on Cu Particles as Dual Protection for Anticorrosion

Jinhua Sun,
Kristoffer Harr Martinsen,
Uta Klement
et al.

Abstract: Although two-dimensional nanosheets like graphene could be ideal atomic coatings to prevent corrosion, it is still controversial whether they are actually effective due to the presence of parasitic effects such as galvanic corrosion. Here, we reported a reduced graphene oxide (RGO) coating strategy to protect sintered Cu metal powders from corrosion by addressing the common galvanic corrosion issue of graphene. A layer of silane molecules, namely, (3-aminopropyl)­triethoxysilane (APTES), is deposited between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Due to the coreshell coating, rGO was uniformly distributed in Cu matrix after sintering, avoiding the aggregation of rGO, that occurs in traditional GO-Cu composite materials. The constant current polarization test by Tafel analysis showed that the dual coating of silane and GO improved the anticorrosion performance of the bulk sample [70].…”
Section: Research Progressmentioning
confidence: 98%
“…Due to the coreshell coating, rGO was uniformly distributed in Cu matrix after sintering, avoiding the aggregation of rGO, that occurs in traditional GO-Cu composite materials. The constant current polarization test by Tafel analysis showed that the dual coating of silane and GO improved the anticorrosion performance of the bulk sample [70].…”
Section: Research Progressmentioning
confidence: 98%
“…The special protective properties of the Znwt.%G/Al coating produced during medium-term immersion can be attributed to equilibrium effect of G. Actually, graphene is a double-edged sword when applied in corrosion protection of a coating [22]. When G completely coats metal surfaces or is us as an additive in organic or inorganic coatings, G prolongs the propagation path of corrosive medium through its large specific surface area; thus, the use of G in the coat mainly plays a role in shielding protection [31,32]. However, the conductivity of G is clined to expedite the metal degradation when G metal matrix composites are used [1 Due to the potential difference between Zn, Al and G, the reaction process of the Zn-G coating in an aggressive medium involves galvanic reactions.…”
Section: Mechanismmentioning
confidence: 99%
“… 13 , 14 We recently reported a surface modification strategy to controllably coat GO on the surface of Cu particles for anticorrosion application. 15 Simple mechanical mixing is not enough to achieve uniform distribution because of the poor interaction. 16 , 17 …”
Section: Introductionmentioning
confidence: 99%